Is It Possible That Marine Based Infrastructure Development is Resolve Inequality Development In the Coastal Community? - Nurul Fatimah; Siti Irene Astuti Dwiningrum (Komunitas, 2023)
Coastal communities are synonymous with poverty problems, both structurally and culturally. Various attempts have been made to solve this problem. One of the most widely carried out efforts is through the construction of infrastructure and supporting facilities for coastal communities. This study aims to determine the reasons why the construction of fishery port infrastructure as supporting facilities for fishing activities was built and how the impact of this infrastructure has on the welfare of coastal communities. The method in this research is qualitative naturalistic. The research subjects are the people who live around the port of Bulu Tuban and who use the port to support their service activities. There are 10 informants in this research consisting of various profiles, from fishermen to bureaucrats related to the construction of the port. Collecting data using observation, interviews and documentation. Data analysis used interactive descriptive qualitative data analysis. The results showed that the port infrastructure development in Bulu village was built on the initiative and appointment of the provincial service based on the opportunity analysis and the needs of the coastal community. The community around the fur fishing port takes advantage of the feather fishing port in their socio-economic activities. Positive changes that occur, such as changing the attitude of the community around the fur fishing port to be more concerned about the environment and shifting of livelihoods. Unwanted changes, with the existence of a large fish auction system, make it difficult for small fish traders to participate in the bid.